Avaliação de impactos sobre as águas subterrâneas da cidade de Sinop/MT e proposta para sua gestão - Boldrin, Mirtes Tatiane Neisse (2012)
The city of Sinop is located in the central north of state of Mato Grosso, distant about 500 km from the capital Cuiabá. With an urban population of 93,735 inhabitants, Sinop depends exclusively on the abstraction of groundwater for public supply. Given this characteristic arises the question: What are the impacts suffered by urban groundwater Sinop/MT? This study aimed to evaluate the impacts on the quantity and quality of groundwater in urban Sinop / MT in order to subsidize the development of a management proposal for this feature. Information on groundwater of Sinop was obtained during a visit to the Autonomous Service of Water & Sewer Sinop, through literature research and work done in the field. The data analysis allowed the knowledge of the characteristics of current and future consumption of groundwater in Sinop. From this information has been prepared an adaptation of Leopold Matrix, specifically to groundwater, which identified and quantified the potential impacts suffered by this feature. It was found that the use of rudimentary wells and cesspools, the cemetery, trade in fuels, the agriculture and city dump are the variables with the greatest risk of groundwater contamination from Sinop. Regarding their quantity have been identified the paving of streets and the dry periods as variables with greater risk of impact. With the information obtained in this work we present a proposal for management specific to groundwater of Sinop. The proposal suggests clear and concise actions that, if implemented by public managers, will ensure water availability in the city of Sinop in quality and quantity.